Development of sprinkler with adjustable orifice using iris-type mechanism for variable rate irrigation - Sobenko, Luiz Ricardo (2019)
Variable rate irrigation intends to supply water identifying \"when\", \"where\" and \"how much\" should be apply, resulting in optimised use of water, increased crop productivity, energy saving and decreased nutrient leaching. Firstly, the concept of an adjustable orifice sprinkler using an iris mechanism actuated by a stepper motor for use in variable rate irrigation was proposed and developed. A prototype was manufactured using additive manufacturing techniques. Its operational characteristics were evaluated. To predict the flow rate, a deterministic model that represented the operation of the sprinkler was proposed and validated. Secondly, to verify the suitability of the water distribution patterns of prototype, rotating and fixed spray plate sprinklers (RSPSs and FSPSs, respectively) were attached to this, each equipped with two different deflector plates, to the mechanism. Tests indoors were performed. Mathematical overlaps were also performed for 2 and 3 m sprinkler spacing. The main results showed that: (1) The observed discharge coefficients varied according to the operating conditions, these being 0.530 when the orifice was fully opened and an average of 0.636 when the iris mechanism reduced the orifice section; (2) for the condition of a partially opened orifice, the phenomenon of jet inversion occurred causing the jet to become asymmetrical; (3) the simulated sprinkling uniformities of lateral line travel were 61.2-91.6% and 88.5-98.7% for FSPSs and RSPSs respectively under different sprinkler spacing conditions; (4) FSPSs presented high potential for surface runoff.